2021
DOI: 10.1007/s00406-021-01259-7
|View full text |Cite
|
Sign up to set email alerts
|

FMRI-based prediction of naltrexone response in alcohol use disorder: a replication study

Abstract: Pharmacological treatment in alcohol use disorder suffers from modest effect sizes. Efforts have been undertaken to identify patient characteristics that help to select individuals that benefit from pharmacological treatment. Previous studies indicated that neural alcohol cue-reactivity (CR) might provide a marker that identifies patients, which benefit from naltrexone treatment.We investigated the reproducibility of the association between ventral striatum (VS) activation and naltrexone (NTX) treatment respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Compulsive drug use occurs after chronic drug use and is often associated with mild to severe SUD, whereas continued drug use despite negative consequences (e.g., innapropriate behavior, belligerence, mood lability, impaired judgment) can be observed in individuals with limited drug intoxication history and is frequently observed in the absence of an SUD diagnosis. While one may argue that the neurobiological mechanisms underlying so-called compulsive-like responding in an individual with limited prior intoxication are relevant for addiction, there is abundant evidence that compulsivelike drug responding with limited drug intoxication may not be driven by the same mechanisms [12] and may not be responsive to the same treatments as compulsive-like drug responding with a history of chronic drug intoxication [13][14][15][16]. In addition, the neurobiological substrates underlying action-outcome associations are likely to differ according to (1) the extent of prior drug exposure and (2) whether or not acute intoxication is associated with negative consequences (which may be immediate or delayed).…”
Section: Issue #2: Drug Use Despite Adverse Consequences In Animals W...mentioning
confidence: 99%
“…Compulsive drug use occurs after chronic drug use and is often associated with mild to severe SUD, whereas continued drug use despite negative consequences (e.g., innapropriate behavior, belligerence, mood lability, impaired judgment) can be observed in individuals with limited drug intoxication history and is frequently observed in the absence of an SUD diagnosis. While one may argue that the neurobiological mechanisms underlying so-called compulsive-like responding in an individual with limited prior intoxication are relevant for addiction, there is abundant evidence that compulsivelike drug responding with limited drug intoxication may not be driven by the same mechanisms [12] and may not be responsive to the same treatments as compulsive-like drug responding with a history of chronic drug intoxication [13][14][15][16]. In addition, the neurobiological substrates underlying action-outcome associations are likely to differ according to (1) the extent of prior drug exposure and (2) whether or not acute intoxication is associated with negative consequences (which may be immediate or delayed).…”
Section: Issue #2: Drug Use Despite Adverse Consequences In Animals W...mentioning
confidence: 99%
“…Then, the COU specification should clarify whether the FDCR-derived biomarker is to be used for diagnostic or prognostic purposes, to select or assess interventions, or as an intervention target (Table; eFigure 8 in the Supplement). This choice should guide the design and interpretation of the biomarker and, ultimately, its validation.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Previous studies in depressed patients reported significant effects of NAc DBS on depressive symptoms, including anhedonia [ 72 74 ]. Furthermore, neuroimaging studies in AUD showed that alcohol-cue-induced brain response in the NAc and the striatum can predict both relapse risk [ 16 ] as well as treatment response to naltrexone [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past neuroimaging studies have uncovered evidence of alcohol-cue exposure increasing brain activation in the NAc and striatum [11][12][13][14]. Brain activation in these areas has been repeatedly demonstrated to be correlated to subjective alcohol craving [11,15], to predict relapse in AUD patients after withdrawal treatment [16,17] and to be associated with a better treatment response to naltrexone, an opioid antagonist [18][19][20].…”
Section: Introductionmentioning
confidence: 99%